Geoelectrical and hydrogeological assessment for the establishment of the relationship between electrical resistivity values and hydraulic properties of aquifer / Safaa Fakhir Yasir - Yasir, Safaa Fakhir (2023)
Hydraulic conductivity, (K) and transmissivity, (T) are considered an important principle for hydraulic characteristic and water flow in soil. Hydrological studies are intrinsic in planning water resources in regional area. Drilling tube well is one of the common techniques for groundwater studies and there are many tests that must be conducted to the characterisation of aquifer such as pumping test which is costly and time-consuming. Usually, to determine the suitable aquifer location, a tube well and minimum of 3 observation wells should be drilled. Geophysical methods are considered an alternative technique where provide a quick and cost-effective technique for mapping subsurface profile imaging. The pumping test data were analysed using the AquiferTest software employing the appropriate solution method. Solution methods used for the pump tests (constant discharge test) included double porosity, Moench Fracture Flow, and Theis. This methodology can be applied to other sites in case pumping test data are available. In this study, vertical and horizontal hydraulic conductivity was determined from electrical resistivity imaging data to evaluate their influence on pumping test results and develop a new relationship between hydraulic conductivity and electrical resistivity for aquifer in Malaysia. Also, to present a relationship for transmissivity with hydraulic conductivity following electrical resistivity. A linear relationship (coefficient of determination R2 = 0.96) was observed between field hydraulic conductivity and electrical resistivity across all field sites. The Nash-Sutcliffe coefficient of efficiency (NSE) was 0.966 and the Mean Absolute Error (MAE) was 0.425. This study was successfully linked hydraulic conductivity with electrical resistivity imaging by using a novel methodology to select the resistivity value. It was concluded that the K-value of an aquifer can be estimated from the electrical resistivity technique. This study concluded also that vertical hydraulic conductivity was closer to the field hydraulic conductivity than horizontal hydraulic conductivity. Hence, estimating hydraulic conductivity from electrical resistivity can provide a non-intrusive, cost and time efficient way to evaluate aquifers of Malaysia.